Lexical and semantic field with a core of “Hoytpak” - Tamara T. Munzuk, Larisa D-O. Shimit, Saida V. Kechil-ool, Oyumaa M-О. Saaya, Irina D-О. Dambyra, Valeriana T. Liktan; Mengi S. Kozhayak, Ayas M. Kongar (Opción, 2019)
The article deals with the syntagmatic links of the hoytpak lexeme, reveals the most common and rarely used words which this lexeme is combined with. Source material for analysis were 20 works of art by Tuvan writers. About 200 examples with the word hoytpakwere collected by the method of continuous sampling. In the course of the analysis, it was determined that with the word hoytpak, the most frequent are combinations of verbs, then combinations with adjectives/participles, the least frequent combinations are combinations with nouns. The use frequency of each word combination is also determined.